Antigen presentation by dendritic cells in rheumatoid arthritis - Rodríguez-Fernández, José Luis (Current topics in medicinal chemistry, 2013)
Rheumatoid Arthritis (RA) is a chronic autoimmune inflammatory disease that affects largely synovial joints. It has been postulated that activated autoreactive CD4 T cells play a key role in triggering and/or maintaining the chronic inflammatory process in RA. Dendritic cells (DCs) are antigen-presenting cells that activate cognate clonal CD4 T cells in the lymph nodes. The activation process involves the formation of a molecular structure at the DC-CD4 T cell contact zone called immunological synapse (IS). In RA, the synovium, a thin layer of tissue below the capsule in the joints, shows a massive infiltration of DCs and CD4 T cells. Subjects bearing HLA-DRB1 alleles of the Major Histocompatibility Complex II gene displaying a motif called RA "shared epitope (SE)", have an enhanced susceptibility to suffer RA. Interestingly, the SE-containing HLA-DRB1 molecules display a pocket with a high affinity for citrullinated antigens, which are found at higher levels in subjects prone to develop RA. Thus, it is possible that the DCs of susceptible individuals may form IS with particular features that may present citrullinated peptides to autorreactive naïve CD4 T clones that, after being activated, contribute to the initiation or development of the disease. Herein I put forward a model of RA initiation based on current information on the immune response and RA.